Pengaruh Pengembangan Usaha Terhadap Peningkatan Penjualan Dengan Kreativitas Bisnis Angkringan Sebagai Variabel Moderating (Studi Kasus Pada Bisnis Angkringan Kaum Millenial di Kecamatan Medan Barat Sumatera Utara) - Azizul Hakim Nugraha (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Angkringan, which is classified as a micro, small, and medium enterprise (MSME), has the potential to contribute to economic growth. Due to its low startup costs and relatively high revenue, angkringan can significantly enhance the economy. This research utilized a quantitative approach, employing the independent variable of Business Development (X), the moderating variable of Business Creativity (Z), and the dependent variable of Sales Improvement (Y). The sample consisted of 32 purposively selected angkringan businesses that had been operating for a minimum of one year. Primary data was collected through the distribution of questionnaires to the respondents. The data analysis techniques included validity tests, reliability tests, descriptive analysis, hypothesis testing, and Moderated Regression Analysis (MRA). The aim of this study was to determine the extent of the impact of business creativity on angkringan sales, providing motivation and insights for future endeavors. The results indicated that business development, moderated by business creativity, had a significantly positive influence on sales improvement. Therefore, it can be concluded that opening a business with creativity holds great potential for increasing sales.